Comparative analysis of naked mole-rat thermogenesis and its potential to maintain euthermia in response to cold - Aleksei Mikhalchenko; June K. Corrigan; Yuchen He; Zalan Peterfi; Sun Hee Yim; Sang-Goo Lee; Zhaoming Deng; Vince G. Amoroso; Vera Gorbunova; Andrei Seluanov; Thomas J. Park; Alexander S. Banks; et al. (Proceedings of the National Academy of Sciences, 2026)
The naked mole-rat (NMR) is a subterranean rodent known for its unique thermal biology, exceptional longevity, and resistance to cancer and hypoxia. However, its thermal biology remains controversial, with various reports describing NMRs as poikilotherms, heterotherms, mesotherms, or partial homeotherms. Here, we investigated whether the thermogenic potential of NMR brown adipose tissue and its UCP1 differ from those in mice and whether the lack of thermal insulation causes extreme changes in NMR body temperature upon cold exposure. Through longitudinal molecular, thermal, metabolic, and behavioral measurements, we found that NMRs initiated nonshivering thermogenesis and elevated body temperature but could not sustain it due to excessive heat loss. Our results suggest that NMRs represent a unique thermoregulatory category that does not fit neatly into traditional classifications. In vitro and in vivo experiments showed that the NMR UCP1 is functional and can be activated and inhibited as expected for most other mammals. We further demonstrated that artificial insulation can partially restore thermoregulatory capabilities in NMRs. This study employs an advanced methodology to characterize the thermal biology of NMRs and helps resolve a long-standing controversy in the field.